2010
DOI: 10.1002/hed.21320
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the combination of ultrasonography and 99mTc‐sestamibi scintigraphy in the preoperative evaluation of uremic secondary hyperparathyroidism

Abstract: The ultrasonography and sestamibi scintigraphy, which showed a higher sensitivity than that of either ultrasonography or scintigraphy alone, led to a reduction of intraoperative frozen sections and to preoperative diagnosis of ectopic (29%) or supernumerary PTGs (10%) and concomitant nodular thyroid disease (24%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 50 publications
5
56
1
1
Order By: Relevance
“…Interoperator coefficients of variation were not studied and are therefore unavailable. According to the reported sensitivity of ultrasonography in SHPT (40), a certain number of parathyroid glands, particularly small ones, might be missed by ultrasound study. It is also possible that a few patients with an ectopic, enlarged parathyroid gland were misclassified into group S or group HS.…”
Section: Discussionmentioning
confidence: 99%
“…Interoperator coefficients of variation were not studied and are therefore unavailable. According to the reported sensitivity of ultrasonography in SHPT (40), a certain number of parathyroid glands, particularly small ones, might be missed by ultrasound study. It is also possible that a few patients with an ectopic, enlarged parathyroid gland were misclassified into group S or group HS.…”
Section: Discussionmentioning
confidence: 99%
“…While the utility of preoperative localizing studies in multigland parathyroid disease associated with secondary HPT has been studied [30][31][32], our study is the first to analyze the utility of preoperative localizing studies in Red and blue dots represent preoperatively identified and confirmed ectopic parathyroid glands to be outside and within the thymus, respectively. Green and black dots represent ectopic parathyroid glands found intraoperatively in the thymus and in the tracheoesophageal (TE) groove, respectively patients with MEN1.…”
Section: Discussionmentioning
confidence: 99%
“…Tecnesyum-99-MIBI sintigrafi+yüksek çözünürlüklü ultrasonografinin duyarlılığı ise % 95 olarak bildirilmiştir (16). Single-photon emission computed tomography (SPECT); diğer bir metod olup özellikle daha önce paratiroid operasyonu geçiren ve re-operasyon planlanan hastalarda ektopik paratiroid dokusunun varlığını görüntülemek amaçlı kullanılan bir yöntemdir (17).…”
Section: Parathormon (Pth)unclassified